Environmental quality of an estuary in Amazon delta using immunohistochemical and morphological analyses of gill as biomarkers - Montes, Caroline da Silva; Ferreira, Maria Auxiliadora Pantoja; Santos, Simone do Socorro Damasceno dos; Rocha, Rossineide Martins (Acta Scientiarum. Biological Sciences, 2015)
In this study, histological, ultrastructural, and immunohistochemical observations of the gill tissue of two fish species (Plagioscion squamosissimus and Lithodoras dorsalis) were used as biomarkers to assess the ecological conditions of an estuary in the Amazon delta, by relating the health status of the fishes to environmental quality. The gill tissue was analyzed both qualitatively and semi-quantitatively. Marked differences in the type and severity of lesions were verified between species and among study sites. A variety of severe damages were confirmed histologically in specimens from the two impacted areas (B and C), including aneurysms, epithelial lifting, and intense hyperplasia. Electron microscopy and immunohistochemical analyses also revealed injuries in the gill tissue of specimens from these two areas. While, on area A only few specimens showed mild changes in gill tissues and rare marking of apoptosis. These results confirm the urgent need for the more effective control of the discharge of pollutants into the estuary as well as more effective urban planning, given the close proximity of a major industrial complex to residential areas.